Integrative Analysis from the Epigenome to Translatome Uncovers Patterns of Dominant Nuclear Regulation during Transient Stress. Issue 11 (13th September 2019) - Lee, Travis A.; Bailey-Serres, Julia
Abstract : Profiling of 11 genome-wide outputs of gene regulation in response to hypoxia reveals multiple aspects of nuclear and whole-cell epigenetic and posttranscriptional gene regulation in Arabidopsis. Abstract: Gene regulation is a dynamic process involving changes ranging from the remodeling of chromatin to preferential translation. To understand integrated nuclear and cytoplasmic gene regulatory dynamics, we performed a survey spanning the epigenome to translatome of Arabidopsis ( Arabidopsis thaliana ) seedlings in response to hypoxia and reoxygenation. This included chromatin assays (examining histones, accessibility, RNA polymerase II [RNAPII], and transcription factor binding) and three RNA assays (nuclear, polyadenylated, and ribosome-associated). Dynamic patterns of nuclear regulation distinguished stress-induced and growth-associated mRNAs. The rapid upregulation of hypoxia-responsive gene transcripts and their preferential translation were generally accompanied by increased chromatin accessibility, RNAPII engagement, and reduced Histone 2A.Z association. Hypoxia promoted a progressive upregulation of heat stress transcripts, as evidenced by RNAPII binding and increased nuclear RNA, with polyadenylated RNA levels only elevated after prolonged stress or reoxygenation. Promoters of rapidly versus progressively upregulated genes were enriched for cis -elements of ethylene-responsive and heat shock factor transcription factors, respectively. Genes associated with growth, including many encoding cytosolic ribosomal proteins, underwent distinct histone modifications, yet retained RNAPII engagement and accumulated nuclear transcripts during the stress. Upon reaeration, progressively upregulated and growth-associated gene transcripts were rapidly mobilized to ribosomes. Thus, multilevel nuclear regulation of nucleosomes, transcript synthesis, accumulation, and translation tailor transient stress responses.